Features of the Concrete Structure of the Structural Element Made by Additive Technology - O. V. Kabantsev; A. V. Karlin (Железобетонные конструкции)
The article discusses the features of the structure of concrete in a structure made using additive technology (3-D printing). The result of the formation of the structure when using the 3-D printing method is investigated. According to the results of experimental studies, the features of the formation of the concrete body of the structure performed using additive technology are revealed.The features of the concrete structure formed in the concrete body when using additive technology are established. The results obtained can be used in the development of methods for experimental studies of effective mechanical characteristics of concrete, as well as in studies to determine the coefficients of concrete working conditions in structures made using additive technology.